Teachers and online education: merits and challenges - Nikitenko, Olga; Malyk, Yuliana (My University, 2021)
Ukraine’s rapid entry into the world and European space, informatization and computerization of society require new knowledge, skills and abilities that would be adapted to the conditions of the information society. The processes related to the informatization of society contribute not only to the acceleration of scientific and technological progress, intellectualization of all human activities, but also to the creation of a new information environment of society that ensures the development of a human’s creative potential. An essential trend in the field of higher education is an increasingly active use of digital technologies and the expansion of online learning formats. Higher educational institutions are obliged to expand their educational activities in the online environment and an increasing number of teachers are involved in the development and delivery of online courses.

Стрімке входження України у світовий та європейський простір, інформатизація та комп’ютеризація суспільства потребують нових знань, умінь та навичок, які були б адаптовані до умов інформаційного суспільства. Процеси, пов’язані з інформатизацією суспільства, сприяють не тільки прискоренню науково-технічного прогресу, інтелектуалізації всієї людської діяльності, а й створенню нового інформаційного середовища суспільства, що забезпечує розвиток творчого потенціалу людини. Суттєвим трендом у сфері вищої освіти є дедалі активніше використання цифрових технологій та розширення онлайн-форматів навчання. Вищі навчальні заклади зобов’язані розширювати свою освітню діяльність в онлайн-середовищі, і все більше викладачів залучаються до розробки та проведення онлайн-курсів.
Keywords: кафедра ділової іноземної мови та міжнародної комунікації; online education; digital technologies; learning technologies; онлайн-освіта; цифрові технології; технології навчання